Peningkatan Hasil Belajar Matematika Melalui Model PBL Berbantuan Media Papan Pobi Kelas IV SD - Rahmawati, Riyantika Diah; Damayani, Aries Tika (STKIP Andi Matappa Pangkep, 2024)
This research uses a Collaborative Classroom Action Research (PTKK) approach which aims to implement the use of the Project-Based Learning (PBL) model and number pattern board media as an effort to improve mathematics learning outcomes in class IV C number pattern material at SDN Karanganyar Gunung 02. Research subjects There are 13 boys and 12 girls in class IV C at SDN Karanganyar Gunung 02. The type of research used is classroom action research (PTK). Each cycle consists of four stages, namely planning, acting, observing and reflecting. Data collection techniques and tools use observation, tests and documentation. The results of the research show that using the Project-Based Learning Model with the help of papa media, number patterns can be a fun learning variation for students so that it is proven to improve student learning outcomes in Class IV C SDN Karanganyar Gunung 02. Before using the Project Based Learning Model ( PBL) student learning outcomes only reached an average score of 68. Then there was an increase after using the Project Based Learning (PBL) Learning Model and the help of a number ball board with an average of 79.6 or 72% in cycle 1 and 88.4 or 92% in cycle 2.